Selling Point Influincer di Sosial Media: Studi Kasus Analisis Resepsi Influincer Keanu Angelo di Kalangan Anak Muda - agustini, vilya dwi (Universitas Muhammadiyah Magelang, 2023)
In the past decade the shift of old media to new media has caused various phenomena. Among other things, the appearance of an influencer or celebrity. Personal branding ability is a necessity to captivate the hearts of the audience.